Prevalence of substance use disorders among prisoners in Al- Diwania governorate, Iraq - Al-Hamzawi, Ali A. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: Substance use disorders (SUDs) are among the common psychiatric disorders and constitute a major public health concern. Iraqi’s were exposed to widespread violence and wars in the last decades. High prevalence of alcohol and substance use was reported recently in Baghdad. Research literature documented the association of SUDs with exposure to trauma events e.g. wars, terrorist attacks and natural disaster. Published articles on SUDs among prisoners in Iraq are scarce. Therefore, this work was carried out to report on SUDs among prisoners in Al-Diwania governorate and its relation to antisocial activity. Methods: A total of 1200 prisoners in Al-Diwania civilian prison were included in the study during the period from 2nd January to 2nd May 2010. A questionnaire using ICD 10 characteristics of SUDs was used. The requested data in addition to characteristics of SUDs were demographic data and type of crime. In order to study the association of SUDs with criminal act, a control group (150 prisoners out of 1050) was selected randomly from the prisoners without SUDs. Results: The study revealed a rate of (12.5%) of SUDs The peak age of abuse was at age 31 – 35 years. More than half of the sample which was composed of male prisoners was in age 25 to 35 years. Fifty three (35.3%) of the abusers were illiterate, and 70 (46.7%) finished the primary school. Only 2 of the abusers (1.3%) had higher education. Thirty (20%) of the abusers were unemployed, 100 (66.67%) were self-employed and only 18 (12%) were employed. Criminal act was significantly associated with SUDs. Conclusion: High rate of SUDs was revealed among prisoners. SUDs were significantly associated with criminal behavior.